Evaluasi Penggunaan Aplikasi Srikandi dalam Efisiensi Kinerja Pegawai pada Bagian Administrasi Pembangunan Sekretariat Daerah Kabupaten Jombang - Riyanti Teressa; Bayu Priambodo (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
This study aims to determine the efficiency of employee performance in the Development Administration Section of the Regional Secretariat of Jombang Regency after using the Srikandi application. A descriptive qualitative approach was used in this study, and data were collected through observation and interviews. The evaluation of the Srikandi application was analyzed using Sedarmayanti's work efficiency theory, which identifies five indicators: timeliness, resource utilization, productivity, quality of results, and cost-effectiveness. The analysis results indicate that the indicators of work efficiency, resource utilization, quality of work results, and cost-effectiveness have successfully contributed to employee efficiency in the Development Administration Section after the implementation of the Srikandi application. However, challenges remain in the timeliness and productivity indicators, with difficulties arising from unstable internet connections and employees' limited ability to operate the application. Therefore, strengthening network infrastructure and providing continuous training are necessary to optimize the use of this application.